Assistance in Creating Google Scholar and SINTA Accounts for New Lecturers in the English Education Department - Sakkir, Geminastiti; Wahyuni, Ika Yuli; Ariyani, Amra; Amin, Fatimah Hidayahni; Adys, Himala Praptami (Yayasan Ahmar Cendekia Indonesia, 2025)
The assistance in creating Google Scholar and SINTA (Science and Technology Index) accounts for new lecturers in the English Education Study Program aims to facilitate them in utilizing these two academic platforms as part of their personal and professional development. Mentoring activities are carried out for one new lecturer, using a lecture method followed by direct practice in creating a Google Scholar and SINTA account. The result of this assistance was the formation of two accounts, which were immediately filled with three articles that had been published and registered in each account and the two accounts were synchronized. This process makes it easy for new lecturers to start their academic digital careers.